Implementation of an Economic Light Duty Three-Axis Computer Numerical Control Machine - Ali A. Abed (SMIEEE); Murtadha A. Al-Ibraheem; Auday A. Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The Computer Numerical Control (CNC) is an advanced technology that has automated many manufacturing applications concerning parts machining as well as other applications. This work presents the implementation of a lowcost desktop size 3-axis CNC machine. It has been built from free software and cheap components. It is able for light duty cutting, painting, carving, and drawing. The control system of the machine consists of a PC and a microcontroller running Grbl software, which is an open source free program. The PC has the task of loading files written in a special programming language for CNCs, which is called G-code. It sends the lines of this file to the microcontroller, which parses the code, interpolates the motion commands, and drives the stepper motors of the machine. The system is built and tested experimentally to prove its operation, robustness, and accuracy.